Memorizing the Quran: Exploring Academic Hardiness, Self-Efficacy, and Perceived Social Support in Islamic Schools - Yundianto, Devie; Khatami, Muhammad; Fathony, Ahmad; Rangkuti, Anna Armeini; Syahputra, Wahyu (Universitas Muhammadiyah Yogyakarta, 2023)
Religion-based schools with a curriculum focused on Quran memorization face challenges in integrating general education with religious education, emphasizing reasoning and memorization. Students must possess academic hardiness to actively participate in learning and develop self-efficacy in memorizing the Quran. Additionally, students require social support to reinforce the impact of academic hardiness on self-efficacy. This research explores the educational and psychological factors that can enhance students' ability to memorize the Quran. The study involved 113 participants, and data were collected using convenience sampling for ease of access. The data were analyzed using moderation analysis with SPSS version 22 and the add-on Macro Process by Hayes. The findings indicated that academic hardiness influences self-efficacy in Quran memorization, with social support playing a moderating role. Specifically, the results revealed that only parental support moderated the influence of academic hardiness on self-efficacy (t (113) = 2.88, p0.01). This research is a valuable reference for family studies, highlighting parents' significant role in their children's academic development. This study's novelty is identifying psychological factors contributing to children's memorization of the Quran.